2021
DOI: 10.1159/000515087
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib Treatment for Refractory PLA2R-Positive Membranous Nephropathy

Abstract: Introduction: B-cell depletion has been shown to be an effective strategy for the majority of patients with membranous nephropathy (MN), and in PLA2R-positive MN, immunologic remission (improvement or elimination of measurable serum anti-PLA2R antibodies) precedes renal remission. Yet, cases exist of patients who do not achieve immunologic remission despite achieving peripheral B-cell depletion. This has led to the hypothesis that some patients have plasma cells that are responsible for producing anti-PLA2R an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Four doses of bortezomib (1.6 mg at days 1, 4, 8, and 11) induced complete remission at 12 months in one patient with primary MN with severe nephrotic syndrome that did not respond to RAS blockade or high-dose corticosteroids, and decreased anti-PLA2R titers, with few AEs [ 57 ]. Similar results with bortezomib plus dexamethasone have been reported in severe and refractory cases to RTX and/or cyclophosphamide [ 58 , 59 ]. However, this therapeutic approach has not been formally tested, and RCTs are required to give more robust recommendations.…”
Section: Unmet Needs and Potential Novel Approachessupporting
confidence: 84%
“…Four doses of bortezomib (1.6 mg at days 1, 4, 8, and 11) induced complete remission at 12 months in one patient with primary MN with severe nephrotic syndrome that did not respond to RAS blockade or high-dose corticosteroids, and decreased anti-PLA2R titers, with few AEs [ 57 ]. Similar results with bortezomib plus dexamethasone have been reported in severe and refractory cases to RTX and/or cyclophosphamide [ 58 , 59 ]. However, this therapeutic approach has not been formally tested, and RCTs are required to give more robust recommendations.…”
Section: Unmet Needs and Potential Novel Approachessupporting
confidence: 84%
“…17 Recently, the potential of proteasome inhibitor bortezomib in treating patients with rituximab-resistant PLA2R-associated MN has been reported. 18 It suggested that plasma cells also produce autoantibodies against podocyte antigens. However, the kidneys may not be main location of IgG4 production because IgG4-positive interstitial cells are rare even in MN with IgG4-positive staining in the glomeruli.…”
Section: Discussionmentioning
confidence: 99%
“… 196 Additionally, case reports have demonstrated that bortezomib usage in refractory MN has resulted in immune and clinical remission. Furthermore, bortezomib treatment has been linked to a reduction in the number of cells producing autoantibodies 197 , 198 , 199 (Figure 6 ).…”
Section: Treatment Strategies For Mnmentioning
confidence: 99%